The Sovereignty of Ulama in Cyberspace: Reconstruction of Ahlul Halli Wal 'Aqdi in the Epistemology of E-Voting - Mohammad Sahrul Tihun; Risno Ibrahim (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Massive digital transformation is driving a fundamental redefinition of the global landscape of Islamic religious authority. However, classical Islamic legal tradition establishes physical presence (al-hudur al-jismani) as a primary prerequisite for the legitimacy of collective decision-making (Ahlul Halli wal ‘Aqdi). This library research using a qualitative-interpretive and interdisciplinary approach aims to reconstruct these normative boundaries to make them compatible with the needs of e-voting in the cyber era. The results of the hermeneutic analysis indicate that the requirement for physical presence in classical texts is instrumental to ensure the quality of deliberation, not the primary objective of sharia (maqashidi primer). Therefore, this article proposes a reconstruction of the concept of deliberative presence (al-hudur al-ta’amuli) as a legitimate constitutive substitute through the mechanism of qiyas ma’na. As a procedural implementation, a three-phase e-voting model is formulated: Pre-Deliberation (At-Tahdhir), Structured Deliberation (Al-Musyawarah Al-Murahhala), and Crystallization & Preferendum (Al-Instijma’ Al-Murahhab). Through comparative analysis, this study finds a systemic epistemological gap in pragmatic digital practices in the MUI, Nahdlatul Ulama, and OIC due to the absence of asynchronous rebuttal mechanisms (ta’qib), open argument logs, and layered preferences. Internal validation confirms that this model is fully compatible with the maqasid al-shari'ah in the aspects of protecting religion, reason, property, and honor, and partially compatible in the dimension of protecting descendants (hifzh al-nasl) which is addressed through the recommendations of the digital sanad protocol. This research provides theoretical contributions as well as practical prescriptions for the governance of global fatwa institutions to be technologically agile without sacrificing the epistemological integrity of Islamic law.